Is neck and shoulder posture, muscle activity and discomfort influenced by tablet inclination in young adults with and without neck pain? - Petcharatana Bhuanantanondh; Siriyaphorn Rungkitlertsakul; Jim Richards (PLoS ONE, 2025)
This study aimed to investigate the effect of tablet inclination on neck and shoulder posture, muscle activity, and discomfort in young adults with and without neck pain during a prolonged writing task. Participants performed a continuous writing task on a tablet for 40 minutes under two conditions, tablet lying flat and with a 30o inclination. The results showed that young adults with neck pain demonstrated higher neck-shoulder muscle activity and discomfort whilst maintaining a similar neck-shoulder posture than those without neck pain. The 30o inclination improved neck-shoulder posture and reduced neck discomfort but induced greater shoulder muscle activity. After 20 minutes, the flat tablet led to increased neck muscle activity in the neck pain group and increased neck discomfort in the group without neck pain. In conclusion, young adults should be recommended to use a 30o inclination and writing on a flat tablet for longer than 20 minutes should be discouraged.